Restorative Justice in The Application of Criminal Acts Through Police Discretion Based on Local Wisdom - Sugiharto, Widodo; Yodo, Sutarman; Sulbadana, Sulbadana (Faculty of Law, Universitas Pekalongan, 2024)
This research aims to: (1) Understand and analyze the application of Discretion by the Police in resolving criminal acts. (2) Understand and analyze whether Police Discretion can be used as a basis for resolving criminal acts based on Restorative Justice. (3) Understand and analyze whether Local Wisdom values can strengthen Discretion in resolving criminal acts based on Restorative Justice. This research uses a normative-empirical research type. The use of this research type is based on the formulation of the problem proposed as a logical consequence of the research legal issue in the background of the problem. This research type is used in accordance with the formulation of the proposed problem. Research results: (1) The application of Discretion by the Police in resolving criminal acts. Criminal law enforcement with the authority of Police Discretion, in its implementation prioritizes the Restorative Justice approach, namely the resolution of criminal cases by involving the perpetrator, victim, perpetrator/victim's family and other related parties to jointly resolve fairly by emphasizing restoration to the original state. (2) Police Discretion can be used as a basis for resolving criminal acts based on Restorative Justice. Discretion based on the Restorative Justice approach is a paradigm that can be used as a framework for handling criminal cases through the conventional criminal justice system in Indonesia. Police Discretion based on Restorative Justice, handling criminal cases based on the National Police Chief Circular Number: SE/8/VII/2018 dated July 27, 2018 concerning the Application of Restorative Justice in the Settlement of Criminal Cases, which serves as a guideline for Investigators in resolving cases through Restorative Justice at the investigation and investigation level. (3) Local Wisdom values can strengthen Discretion in resolving criminal acts based on Restorative Justice. The revitalization of Local Wisdom is a strategy used to revive community traditions and culture so that they can be used as an alternative by the Police in resolving criminal acts. Through Restorative Justice originating from Police Discretion.